The ICJ Whaling Case: missed opportunity to advance the rule of law in resolving science-related disputes in global commons? - Brendan Gogarty; Peter Lawrence (2017)
A number of treaties relating to the global commons include provisions which rely on science, or scientific research, without defining these terms (e.g. climate change, Antarctica). Disputes relating to what counts as genuine science and/or the appropriate responses to science are a feature of these regimes. Against this context, the Whaling Case before the International Court of Justice (ICJ) created hopes that the court would advance the rule of law by interpreting the concept of "scientific research" under the Whaling Convention. We argue that the court missed an opportunity by adopting a narrow approach which involved assessing the Japanese whaling programme in terms of its own objectives, by use of a standard of review test extracted from World Trade Organization (WTO) jurisprudence. On close inspection the ICJ implicitly adopted a definition of science while maintaining that it was doing no such thing. We argue that the Court should have proceeded to interpret scientific research under Art. VIII of the Whaling Convention applying the international law rules on treaty interpretation and informed by direct evidence from scientific experts which it is entitled to call on under its Statute. The Whaling Case thus represented a missed opportunity.